Laparoscopic distal pancreatectomy for benign and malignant disease: a review of techniques and results - Danilo Coco; Silvana Leanza; Riccardo Schillaci; Giuseppe Angelo Reina (Gastroenterology Review)
Diagnosis of pancreatic cancer is challenging in the initial phases because its progression is rapid. The pancreatic tail and body roughly accounts for 20–30% of all cancerous cases. The standard treatment for symptomatic benign, malignant, and premalignant diseases of the pancreatic tail and body is distal pancreatectomy. This technique has been modified over the years to fit certain indications, with the goal of enhancing post-operative results as well as reducing patient trauma. In cases of a premalignant and symptomatic benign condition, the spleen must be preserved either using Kimura’s splenic vessel preservation technique or Warshaw’s splenic vessel resection technique. A better long-term prognosis is ensured by regional lymph node dissection and radical R0 resection. Radical antegrade modular pancreatosplenectomy was proposed to tackle the shortcomings of traditional surgery for pancreatic tail and body cancer. In this review, study techniques and results of laparoscopic distal pancreatectomy for malignant and benign pancreatic ailments were described with the intention of providing knowledge on various suitable techniques reported for pancreatic cancer treatment. Furthermore, this study will serve as a ready reckoner for surgeons and could serve to boost their confidence levels during surgery by avoiding confusion on the selection of suitable for the pancreatic diseases diagnosed.